Brain glucose and ketone metabolism in first-episode psychosis: Neuroimaging and brain metabolism before and after antipsychotic treatment: The protocol for the CAST-ATP study - Kevin Zemmour; Guy-Olivier Samson; Mélanie Fortier; Eliot Parent; Alexandra Leus; Sylvain Grignon; Jean-Daniel Carrier; Kevin Whittingstall; Andreas Aalkjær Danielsen; Ole Köhler-Forsberg; Allan Kjeldsen Hansen; Sri Mahavir Agarwal; et al. (PLoS ONE, 2025)
First episode of psychosis (FEP) has an early onset and is associated with significant functional impairment, loss of productivity and premature cardiovascular disease. Antipsychotics (AP) remain the cornerstone treatment of FEP yet they fail to improve key symptom domains and contribute to the metabolic burden of this disorder. A growing body of evidence suggests that a metabolic deficit in the brain, specifically of glucose, at the earliest stages of illness could represent an etiopathological phenotype of FEP. Correcting this metabolic deficit could improve outcomes and disease course. The acronym for this study is CAST-ATP for the collaboration between our clinical research sites in Copenhagen, Aarhus, Sherbrooke and Toronto, on the subject of Antipsychotic (AP) treatment, PET and Psychosis. The main aims of CAST-ATP are to evaluate the effect of 1) a diagnosis of FEP, and, 2) 4–6 weeks of AP treatment on brain energy metabolism measured by PET scans (uptake of ketones and glucose). The hypothesis is that (i) glucose metabolism will be impaired in AP-naïve patients as compared to healthy controls, and (ii) this defect will be worsened by AP. In contrast, across the two aims, brain ketone metabolism is predicted to not be significantly influenced by FEP or AP treatment. Participants on both sites will undergo an imaging protocol (PET scans + MRI) in addition to measures of psychopathology and related peripheral metabolic, inflammatory and hormonal markers. If our hypothesis is confirmed, it will reinforce the strategy to leverage ketone supplementation to improve symptoms, functioning and quality of life by bypassing the brain glucose deficit in FEP. As such, this should be a significant therapeutic development. To this last point, the pharmaceutical treatment of schizophrenia spectrum disorders has not progressed beyond currently available AP for over seven decades.